Learning Citizenship Education as an Effort Improving Children's Morality - Yulia Abdul Nasution (International Journal of Students Education, 2024)
This study aim for develop morality children who have decrease for build generation successor in possession morality in accordance with the morals of Indonesian citizens through Citizenship Education learning in schools. Research methods using research literature. This study use literature review method or literature study with do search results study from a number of relevant journals with the problem studied like from indexers Google Scholar, Sinta, Basicedu, Hafecs, and so on. This data will be processed for produce information new one can useful for future readers. Data used in this study is secondary data Because methodology used is studies References. Deep data collection techniques this study form collecting library data, reading, and taking notes as well as process material study. Data obtained is the data taken from study previous i.e. on a range 5 years time final. Result of this study that developments over time, environment place play, and parental guidance very influence to development morality child and learning Citizenship Education can be one increase morality child.